The Duality of Structure Behind the Practice of Reporting in Perpetuating the Existence of Corporations - MT. Sirait, Charles Bonar; Widaningsih, Titi; Dua, Michael; Rusadi, Udi (Enrichment: Journal of Multidisciplinary Research and Development, 2024)
This research aims to reveal the duality of the structure carried out by MNC Group through Okezone.com in news related to the Broadcasting Bill. The delay in the ratification of the Broadcasting Law No. 32 of 2002 is the background for the dominance of media discourse by MNC Group which fights for a Multi Mux or Hybrid Mux system that is more beneficial to them than the government-supported Single Mux model. This research uses a critical paradigm with a qualitative approach based on Anthony Giddens' structural theory and Teun A. van Dijk's critical discourse analysis. The results of the study show that 12 news articles in Okezone.com throughout 2017–2018 reflect the dominance of MNC Group in building public opinion to support the Multi Mux system. The duality of structures is seen in three dimensions: significance, dominance, and legitimacy, which systematically intervene in the public space. This research highlights that economic-political motives are the main drivers, where the power of the media is used to marginalize the public interest for the benefit of certain groups. This study concludes that the power of the media supported by the socio-political structure has the potential to threaten the balance of information and democracy in the Indonesian broadcasting ecosystem.